The ‘police progression paradox’? Why are women under-represented across the middle ranks of the police? - Bailey, Louis (Policing and society, 2025)
Internationally, despite increasing numbers of women entering the police, women are still under-represented across the various ranks of law enforcement, especially within more senior and leadership positions. Barriers to women’s progression within law enforcement has been identified in previous research; however, what is not known are the reasons behind the drop in representation of women officers across the middle tiers of the police; an important promotion stage likely to hinder women entering senior ranks. This article seeks to address this significant dearth in knowledge, by presenting the findings of a large-scale mixed-methods research project exploring staff retention and, in particular, the experiences and barriers faced by women officers. The resulting research comprises three parts: (i) statistical analyses of national workforce data on 142,505 police officers in England and Wales, (ii) in-depth examination of one constabulary’s HR data pertaining to 3321 officers, and (iii) force-wide semi-structured interviews with women officers (n = 9). Each method targets a unique level of ecology (cultural/national; organisational, and individual) and draws on complexity theory to provide a multi-level exploration of the issues and barriers preventing women from progressing in their policing careers. Central here is an examination of the gendering of the police organisation and the ways in which gender performance, stereotypes, bias, and expectations filter through to working relationships and policing hierarchies vis-a-vis the social and domestic sphere. We argue that focusing only on women’s overall representation in the police, creates a ‘police progression paradox’ which masks the underlying problem of women’s progression into senior roles.